A Corpus-Based Study On Gender- Related Differences In Deontic Modality Markers Used In Commencement Remarks By American Speakers - Đỗ Thị Duy An (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis aims to investigate the differences in the employment of deontic modality markers in commencement speeches by American speakers regarding their syntactic features, semantic categories and pragmatic functions. In order to conduct the study, the corpora of 100 commencement speeches by male and female speakers are built. Both qualitative and quantitative research methods were adopted on the basis of corpus- based method in collecting the data. Results of data analysis in the thesis reveal that frequency use of deontic modality markers between the male and female corpora experience some significant differences regarding a wide range of modal auxiliaries or other modal lexical verbs as well as non-auxiliary modals such as modal adverbs, modal adjectives, modal nouns, imperative sentence and if[1]clause. Additionally, men incline towards modal adjectives, modal auxiliary verbs and quasi modal verbs whereas female prefer modal nouns, modal lexical verbs and If clause. Semantically, female speakers express stronger pledges toward students while male speakers enforce more participant oriented obligation on the hearers. The results also show that female prefer adhortative to urge the graduates to perform some desired actions whereas male speakers opt for cohortative by engaging both speaker and hearer under mutual encouragement. However, there are no remarkable differences in expressing strong necessity by using modal adjectives between two corpora. In relation to pragmatic functions, both male and female speakers adopt bald-on record, positive and negative politeness strategies. Female speakers employ more clausal mitigator- conditional sentence and inclusive We as mitigation markers than female counterparts although marker please is used equally between two groups of speakers.